Design of atmospheric composition monitor based on ultraviolet optical absorption technology - 李文军 (Optoelectronics letters, 2011)
An open path atmospheric composition monitor is designed based on ultraviolet differential absorption technology. Dark current correction and diode response correction are used to improve the detection limit and Savitzky-Golay filter is used to improve the measurement accuracy. The experimental results show that the designed system has the ability to measure NO and NO2 in real time with reasonable accuracy. The detection limit of the system is about 0.25 ppm for NO and 0.28 ppm for NO2. When the concentration level of the target gases is below 100 pprn, the system has good linearity and high measurement accuracy, i.e., the measurement accuracy is about 2% for NO and about 4% for NO2. The detection limit of dark current can be improved by about 5 to 10 ppb, and the correction of diode response can improve the detection limit by around 30 ppb. Moving window average can improve the detection limit at low concentration levels but will generate more errors at higher concentration levels. Generally, the designed system meets the requirement of measuring multi-species air pollutants in real time and accurately.